Optimization Of Fluidised Bed Granulation Process Parameters For Urea Granule Manufacturing Using The Response Surface Method - Zainal Abidin, Mohammad Anas; Dimin @ Mohd Amin, Mohd Fairuz; Said, Md Radzai; Se, Sian Meng; Shaaban, Azizah; Abd Rahman, Md Nizam (Trans Tech Publications Ltd., 2017)
Fluidised bed technology is commonly applied in the pharmaceutical, agricultural and food production technology. The aim of this work is to identify the optimum process parameters in order to gain the best hardness and density values for the urea granules from the fluidised bed granulation. The layout of the experiments are based on Central Composite Design of Response Surface Method. The analyzed data shown that the optimize value for each of these parameter are 0.10MPa, 32.11Hz, 50% w/w, 42.25°C for spray pressure, fan speed, urea solution concentration and inlet air temperature with 1.71 kgf/granule hardness and 1.85 g/cm3 density were predicted. Experimentally, using the predicted optimize input parameter, the hardness and density observed were 0.20 kgf/granule and 1.30 g/cm3 respectively.